Synthesis, Bonding and Reactivity of a Terminal Titanium Alkylidene Hydrazido Compound. Issue 13 (11th February 2013) - Tiong, Pei Jen; Groom, Laura R.; Clot, Eric; Mountford, Philip
Abstract We report a detailed study of the reactions of the TiNNCPh2 alkylidene hydrazide functional group in [Cp*Ti{MeC(NiPr)2}(NNCPh2)] (8) with a variety of unsaturated and saturated substrates. Compound 8 was prepared from [Cp*Ti{MeC(NiPr)2}(NtBu)] and Ph2CNNH2. DFT calculations were used to determine the nature of the bonding for the TiNNCPh2 moiety in 8 and in the previously reported [Cp2Ti(NNCPh2)(PMe3)]. Reaction of 8 with CO2 gave dimeric [(Cp*Ti{MeC(NiPr)2}{μ‐OC(NNCPh2)O})2] and the "double‐insertion" dicarboxylate species [Cp*Ti‐{MeC(NiPr)2}{OC(O)N(NCPh2)C(O)O}] through an initial [2+2] cycloaddition product [Cp*Ti{MeC(NiPr)2}{N(NCPh2)C(O)O}], the congener of which could be isolated in the corresponding reaction with CS2. The reaction with isocyanates or isothiocyanates tBuNCO or ArNCE (Ar=Tol or 2, 6‐C6H3iPr2; E=O, S) gave either complete NNCPh2 transfer, [2+2] cycloaddition to TiNα or single‐ or double‐substrate insertion into the TiNα bond. The treatment of 8 with isonitriles RNC (R=tBu or Xyl) formed σ‐adducts [Cp*Ti{MeC(NiPr)2}(NNCPh2)(CNR)]. With ArF5CCH (ArF5=C6F5) the [2+2] cycloaddition product [Cp*Ti{MeC(NiPr)2}{N(NCPh2)C(ArF5)C(H)}] was formed, whereas with benzonitriles ArCN (Ar=Ph or ArF5) two equivalents of substrate were coupled in a head‐to‐tail manner across the TiNα bond to form [Cp*Ti{MeC(NiPr)2}{N(NCPh2)C(Ar)NC(Ar)N}]. Treatment of 8 with RSiH3 (R=aryl or Bu) or Ph2SiH2 gave [Cp*Ti{MeC(NiPr)2}{N(SiHRR′)N(CHPh2)}] (R′=H or Ph) through net 1, 3‐addition of SiH to the NNCPh2 linkage of 8, whereas reaction with PhSiH2X (X=Cl, Br) led to the TiNα 1, 2‐addition products [Cp*Ti{MeC(NiPr)2}(X){N(NCPh2)SiH2Ph}].